PENGARUH KETERLIBATAN ORANG TUA TERHADAP MOTIVASI BELAJAR SISWA KELAS IV DAN V MI ALAM ISLAMIC CENTER PONOROGO - Andik Muhammad Rofi’i; Happy Susanto; Ayok Aryanto (TARBAWI:Journal on Islamic Education, 2020)
This study aims to determine the influence of parental involvement on the learning motivation of grade IV and V students at MI Alam Islamic Center Ponorogo. In this study, the total population was 42 students in class IV and V of MI Alam Islamic Center Ponorogo which included 11 children in class IV A, 12 children in class IV B, and 19 in class V. Because the number of class IV and V MI Alam Islamic Center Ponorogo is 42 students, the population sample in this study is all of them. In measuring the research variables, the researcher first tested the instrument, namely the validity test and the reliability test. Meanwhile, in measuring the effect of the two variables using the correlation formula and simple linear regression using SPSS 20 to determine the results of the data that has been done. Based on the data processing that has been done, there is a significant influence between the involvement of parents on student motivation at MI Alam Islamic Center Ponorogo amounting to 32.7% while the remaining 67.3% is influenced by other aspects